Studies on the Therapeutic Approaches for Uterine Torsion in Surti Buffaloes (Bubalus bubalis) - Satish; Gaur, Mitesh (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The present study was conducted on 55 pregnant torsion affected Surti buffaloes presented to VCC of the College, Navania (Udaipur). Three types of therapeutic approaches were used, viz., ‘simple rolling of the dam’ (n=14), Sharma’s modified Schaffer’s technique (n=41) and Caesarean Section (n=20/41) with the success rate of 100 %, 51.22 % and 36.36 %, respectively. On an average 1-4 rolling were tried and then CS was performed. The survival rate of dam following vaginal delivery and CS was 94.28 (33/35) and 80.00 (16/20) %, respectively. The overall rate of survival for dam and fetus was 89.09 (49/55) and 9.09 (5/55), respectively. The success rate was better for cases with less degree of torsion (up to 180°). The birth ratio among the affected cases for male and female was 58:42, suggesting male fetus as one of the predisposing causes of torsion in buffalo.